INNOVATE TO ELIVATE: UNVEILING THE MEDIATING ROLE OF GREEN INNOVATION BETWEEN CORPORATE SOCIAL RESPONSIBILITY AND ENVIRONMENTAL PERFORMANCE: A STUDY OF KHYBER PAKHTUNKHWA MANUFACTURING INDUSTRIES - Muhammad Ishaq; Abdul Hameed Khan; Azhar Farid; Taimoor Ali Shah (International Journal of Contemporary Issues in Social Sciences, 2024)
Objectives: The main objective of the study was to investigate the strategies used to improve "organisational environmental performance" (EP). The research addresses the significant role of corporate social responsibility CSR in relation to the environmental performance of organizations. It operates systematically gathering and analyzing existing literature using the legitimacy theory. Method: The present research investigates the association between CSR and EP. Green innovation GI as mediator in the study was explored. 250 participants from manufacturing industries were selected for the data collection. Results: The study's findings revealed that CSR has positive and significant effect on environmental performance. Furthermore, green innovation partially mediates the stated relationship. Implications: The study's findings align with the suggested mediation framework. In the developing country, the CSR practices is a novel concept, and more study is required to identify issues related to sustainability and evaluate the effects of CSR practices in manufacturing sectors.